Tratamiento fisioterapéutico en pacientes con enfermedad de Server. - Araujo Chavez, Miguel Angel (2024)
The present investigation was of a documentary type, scientific articles selected from various bibliographic sources were used, where its objective was to demonstrate the effectiveness of physiotherapy to help pediatric patients with Sever's disease where children have been affected in carrying out their daily activities or even just playing. Physiotherapy or physical therapy being a therapeutic method in charge of reducing the tension exerted on the calcaneus helps by means of exercises, stretching, mobilizations, this depends on the severity of the injury and the characteristics of the patient, to indicate or execute various interventions. In the research methodology, 40 scientific articles were analyzed, 35 were selected in different languages, Spanish and English: the databases in which information was found were Scielo, Dialnet, Pubmed, each of the 35 articles was validated using parameters of the PEDro scale, which helped to identify the results that this physiotherapeutic treatment provides to patients with Sever's disease. As a conclusion of this research, it can be noted that physiotherapy is of great importance for patients with Sever's disease since the physical activity that has been evidenced gives us as a positive result in help and improvement in activities such as running, jumping, or playing, avoiding the damage in growth cartilage and managing to observe that the patient gets pain relief, improvement in the process of oedematisation, and functional restriction of daily activities.